2013
DOI: 10.1096/fj.13-237941
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sec14‐like 3 as a novel lipid‐packing sensor in the lung

Abstract: Pulmonary surfactant, a complex composed primarily of lipids and associated proteins, is synthesized in alveolar type II (ATII) cells and secreted into alveoli to prevent collapse during respiration. Although numerous studies have clarified the fundamental roles of pulmonary surfactant, the molecular mechanisms of transport and secretion of pulmonary surfactant remain totally unknown. Thus, we screened candidate genes by comparing genes with the expressed sequence tag (EST) libraries of embryonic and adult lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Nonenzymic proteins capable of binding lipids exist for a variety of different purposes within cells, as evidenced by a host of recent publications (Blind et al 2014; De Libero & Mori, 2012; Drin, 2014; Garzón et al 2013; Hashikawa et al 2013; Holthuis & Menon, 2014; Kono et al 2013; Luoma et al 2014; Maceyka & Spiegel, 2014; Maeda et al 2013; Mesmin et al 2013; Olkkonen & Li, 2013; Ren et al 2014; Roulin et al 2014; Sandhoff & Harzer, 2013; Schulze & Sandhoff, 2014). The purposes include: (i) presentation of lipids to hydrolytic proteins for degradation and salvage of breakdown products to rebuild and recycle needed lipid components; (ii) presentation of lipids to proteins of the immune system during development of antigenicity; (iii) sensing of intracellular lipid compositions in membranes of various organelles; and (iv) transfer of lipids between intracellular membranes of different organelles.…”
Section: Introductionmentioning
confidence: 99%
“…Nonenzymic proteins capable of binding lipids exist for a variety of different purposes within cells, as evidenced by a host of recent publications (Blind et al 2014; De Libero & Mori, 2012; Drin, 2014; Garzón et al 2013; Hashikawa et al 2013; Holthuis & Menon, 2014; Kono et al 2013; Luoma et al 2014; Maceyka & Spiegel, 2014; Maeda et al 2013; Mesmin et al 2013; Olkkonen & Li, 2013; Ren et al 2014; Roulin et al 2014; Sandhoff & Harzer, 2013; Schulze & Sandhoff, 2014). The purposes include: (i) presentation of lipids to hydrolytic proteins for degradation and salvage of breakdown products to rebuild and recycle needed lipid components; (ii) presentation of lipids to proteins of the immune system during development of antigenicity; (iii) sensing of intracellular lipid compositions in membranes of various organelles; and (iv) transfer of lipids between intracellular membranes of different organelles.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the CRE-element in the Sec14l3 promoter is evolutionary highly conserved, suggesting functional relevance. Little is known regarding functions of Sec14l3, which is highly induced around birth in lung tissue51. In mammalians more than 20 Sec14 family members have been described, carrying highly conserved lipid-binding domains52.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalians more than 20 Sec14 family members have been described, carrying highly conserved lipid-binding domains52. Sec14l3 has been specifically implicated in the intracellular transport of α-tocopherol53 and has been proposed as sensor of liposomal lipid-packing defects in the lung51. Human SEC14L3 has been found to be decreased in bronchial and nasal epithelium of smokers54 and during human rhinovirus infection55.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Hishikawa et al (68) have identified Sec14L3 as a phospholipid transporter in alveolar type II cells. Sec14L3, a Sec14 homolog, not only has an expression pattern similar to LPCAT1 and StarD10 but also binds to a variety of PC species.…”
Section: Discussionmentioning
confidence: 99%